A contradição ensino, aprendizagem e desenvolvimento na educação infantil : a atividade de ensino na perspectiva da pedagogia histórico-crítica e da psicologia histórico-cultural - Bezerra, Mayam de Andrade (2024)
This research was developed from the perspective of Historical-Critical Pedagogy and Historical-Cultural Psychology regarding the teaching activity and the child’s activity in the development of the psyche. To this end, we problematize the conceptions that deny school education, stigmatize teaching and defend naturalizing and spontaneous perspectives concerning child development. In this context, this research aims to understand the conception of Childhood Education teachers about the relationship teaching, learning and development from the perspective of Historical-Critical Pedagogy and Historical-Cultural Psychology. We started from an approach to social practice, based on the philosophical and methodological foundations of historical-dialectical materialism, which attempts to understand the object of study in its historicity, recognizing its historical movement, its genesis and its transformation. Based on this method, we seek to capture the structure and dynamics of the investigated object, revealing its real connections and objective relationships present in the dialectical unity between the teaching activity and the main activity of the child, in order to be able to understand the phenomenon in its multiple determinations. Thus, we confirm the thesis that the conception of teaching, linked to the perspective of historical-critical pedagogy and historical-cultural psychology, enables the Early Childhood Education teacher's understanding of the enhancing role of teaching in the activity of the child and the development of maximum child capabilities.The empirical research was performed in the years of 2022 ad 2023, with 12 (twelve) Childhood Education teachers who work in Municipal Childhood Education Centers in the municipal system of João Pessoa-PB. The semi-structure interview was the main instrument used to collect information. The discourses of the research subjects highlighted the existence of a stigmatization of teaching, especially at this educational stage, linking it to traditional pedagogy and the mere transmission of mechanical knowledge, as well as pointing to a process of construction of identity of Childhood Education crossed by contradictions and permeated by conceptions about the learning process and child development based on naturalizing and spontaneous perspectives that further reinforce the precariousness of pedagogical work and the theoretical fragility of teacher formation. In a context characterized by the denial of the activity of teaching as a process of intentional and conscious intervention by the teacher to promote the development of the child psyche, it becomes even more urgent for the teacher to understand the importance to organize teaching, aiming to conduct the main activity thar guides the child’s development, in order to mobilize not only the capacities and psychic processes already formed and consolidated in the child psyche, but those that present themselves as imminent possibility of development. Finally, it is essential that the child’s activity is organized towards the development of new affective-cognitive abilities, through a developmental teaching process in Childhood Education.